Módulo autónomo de bajo costo para monitoreo de la calidad del aire. (2020)
The concentration of particulate matter (PM) with aerodynamic diameter <10μm (PM10) and <2.5μm (PM2.5) are parameters widely used to determine the level of pollution in the air we breathe. Based on a project of Citizen Science https://luftdaten.info born in Stuttgart (Germany), a prototype will be used to measure PM with low-cost sensors. The air quality measurements are made through a node and sent to the Luftdaten web platform, where they can be analyzed. These modules communicate with the website Luftdaten.info which receives all the data taken by the module and projects it. The communication protocol used by the module is Wi-Fi. The aim of the project is to successfully replace the Wi-Fi protocol with the LoRaWAN protocol. The solution initially proposed consists of a SDS011 particulate material sensor, a DHT22 temperature and relative humidity sensor, an Arduino Mega 2560 R3 controller and the LoRa RHF76-052 chip. The devices are connected to the Arduino and through a developed code the data is sent to the LoRa LG02 Gateway. This proposal presented difficulties at the time of assembly, because the LoRas used presented difficulties in communicating. Due to the inconveniences presented with the chip, it was decided to take the proposal presented by Luftdaten. This proposal consists of using an Arduino module integrated with a LoRa chip. This type of proposal, although more reliable, because errors like those presented in the original idea do not happen, is usually more expensive. The module measures and sends the data every 15 minutes. The Gateway will receive the data sent by the LoRa and will forward it to TTN where the received data can be viewed. In turn, TTN forwards this information to a server where a Python code is executed. This code uses the Luftdaten.info API to forward the information.